Mechanical Strength and Degree of Polymerization of Oil-paper Non-wood Kenaf Bast Fiber as New Transformer Insulation Presspaper - Nurul ‘Izzati Binti Hashim; Mohd Taufiq Ishak; Mohd Taufik Jusoh Tajudin; Ja’afar Adnan; Anis Shahida Niza Mokhtar; Nur Sabrina Suhaimi; Nadira Johari Halim Shah Ayob (Akademia Baru Publishing, 2025)
Non Indexed Publication (Tier 4)